Identification of biomarkers associated with CD8+ T cells in rheumatoid arthritis and their pan-cancer analysis - Zhao, Zhenyu; Ren, Jie; Xie, Siping; Zou, Longchun; Zhao, Qianyue; Zeng, Shan; Zha, Dingsheng (Frontiers in Immunology, 2022)
Rheumatoid arthritis (RA), a prevailing chronic progressive autoimmune disease, seriously affects the patient's quality of life. However, there is still a lack of precise treatment and management methods in clinical practice. Previous studies showed that CD8+ T cells take a lead in the progression of RA. Thus in this study, 10 genes were identified to be closely related to CD8+T cells in RA through multiple RA datasets, CIBERSORT, and WGCNA algorithms. Further machine learning analysis identified 3 CD8+T cell-related genes most closely related to RA: CD8A, GZMA, and PRF1. In addition, the relationship between these three key genes and 33 cancer species was also explored in this study. Our research aims to provide new ideas for the clinical treatment of RA.